Auguste Comte : an intellectual biography. - Pickering, Mary (Cambridge University Press, 2009)
This volume explores the life and works of Auguste Comte from 1842 to 1852, when he transformed his philosophy into a religious and political movement.
Keywords: Comte, Auguste, -- 1798-1857.; Comte, Auguste, -- 1798-1857; Philosophers -- France -- Biography.; Philosophes -- France -- Biographies.; Philosophers; France; Biographies; Biographies.